Improving English Grammar Skills Through Islamic Content and Technology for Secondary School Students in Islamic Boarding Schools - Jarum, Jarum; Farah, Rafika Rabba (JOLLT Journal of Languages and Language Teaching, 2026)
Mastering English grammar is essential for effective communication, academic success, and professional growth. As one important language element, grammar helps learners in expressing ideas more clearly, avoiding misunderstanding, and engaging in meaningful interactions. Yet, many secondary school students in Islamic boarding schools (pesantren) face challenges in mastering grammar due to traditional teaching methods and a lack of engaging learning sources. This study examines the effectiveness of integrating Islamic content and technology into English grammar teaching to enhance students’ learning experiences and outcomes. In particular, the research investigates the impact of the Quizizz platform as an interactive gamified learning tool for grammar instruction. A pre-experimental design with pre- and post-tests was employed to measure the student’s progress in grammar proficiency after exposure to Islamic content-based instruction and interactive digital platforms such as Quizizz. In its statistical analysis, the test results revealed a significant improvement in grammar proficiency, with an Asymp.Sig. (2-tailed) value of 0.000 < 0.05, confirming the hypothesis that using Quizizz positively impacts student learning outcomes. The findings demonstrate that integrating technology into grammar instruction can enhance engagement, understanding, and application of grammar concepts. This study underscores the potential integrating religious content with technology-driven instruction to facilitate effective grammar learning in Islamic boarding school settings. Future studies with broader sample sizes, long-term treatment, and control group comparison is needed to strengthen the generalizability of the research results.